Compressive Strength and Water Absorption of Concrete Containing Foundry Sand as Fine Aggregate Replacement - Shaiful Azman, Muhammad Syakir Khalafee; Jamellodin, Zalipah (Recent Trends in Civil Engineering and Built Environment, 2023)
Foundry sand is a high-quality silica sand that is pure, evenly sized, and used in foundry casting processes. In the foundry sand process, sand from finished metal castings is very often reused. Foundry sand was being used as a moulding casting material for ages. Sand is one of the most difficult wastes and less recyclable especially in Malaysia and it require a massive amount of energy and cost while through the process to produce mould. Concrete, which is mostly made up of fine aggregate, is one of the most often used materials in the building industry. This objective of this study is to determine the behavior of concrete that used waste foundry sand as fine aggregates. There are several percentages of WFS that were used in this study, which is 10, 20, 30 and 40%. Every mix proportion give different result toward concrete behavior. From the sieve analysis test, the percentages of waste foundry sand (WFS) have passed the specification of size distribution according to the British Standard. The highest slump value is 45mm with replacement of 30% WFS, beyond that the slump value will drop but still acceptable. The strength of the concrete is increase when 10% of WFS of foundry sand was used for 7 and 28-days curing. The highest value compressive strength is 23.40 Mpa and 36.12 Mpa for 7 and 28 days. The increasing amount of WFS replacement will increase the percentage of water absorption. Referring to the result, the 40% of WFS is still acceptable for water absorption. As conclusion from this study the optimum percentage of WFS is 10% was improve the concrete strength.